Pemanfaatan dan langkah langkah pembuatan surat lamaran kerja dan CV pada MS Word - Syahlaa Maulana; Rahma Fahmadina Lubis; Nurleli Nurleli; Nurbaiti Nurbaiti (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study attempts to investigate technical advancements in the nation, which cannot be compared to developed nations but has a great deal of potential for natural and human resources. A minimum level of basic knowledge of sophisticated information processing tools has been required for decades, and has even expanded in this century, especially "Computers," in order for human resources to access information sources in the era of globalization. In the modern era, using a computer at work has become a must. In addition to understanding the fundamentals of Microsoft Word, we can use this application to create a job application letter to boost the advantages. enhancing the standard of knowledge